BABY MASSAGE ASSISTANCE IMPROVES SLEEP QUALITY AND GROWTH OF LOW BIRTH WEIGHT BABIES IN SAMARINDA CITY - Andi Lis Arming Gandini, Andi Ummu Salmah, A.Arsunan Arsin, Stang, Aminuddin Syam, Muhammad Tahir Abdullah, Syamsiar S. Russeng, Santi Martini (Chelonian Research Foundation, 2024)
Introduction: Low birth weight (LBW) is defined as a birth weight of less than 2.5 kilograms regardless of the neonate's gestational age, according to the World Health Organization (WHO). Indonesia is in the highest ranking in Southeast Asia, with an LBW percentage of more than 9.9%, which amounts to around 450 thousand births annually (WHO, 2023). Research in Wuhan, China, shows that babies with LBW are at risk of experiencing delays in motor development. One of the factors that influence a baby's growth is sleep and rest. Baby massage is an intervention that involves stroking using different movements uniformly throughout the baby's body. Baby massages have many benefits, including increasing body weight. Other research also proves that babies who are massaged have regular sleep patterns. Method: This type of research is quantitative, with a Quasi-Experimental Nonequivalent Control Group Design. The sample consisted of 36 breastfeeding mothers divided into 2 groups: the intervention and the control groups. In this research, the experimental group was given baby massage assistance, and the control group was given education via Zoom. Results: There were differences in LBW babies' growth, improved sleep quality before and after baby massage assistance in the intervention group, and education via Zoom in the control group. Discussion: Various efforts have been made to increase growth in LBW babies, one of which is by assisting with baby massage. A massaged baby will feel comfortable so that the baby can sleep longer, and the quality of the baby's sleep will improve. Sleep quality has a vital role in the growth of LBW babies. Babies with good quality sleep according to age will significantly impact their growth and development. Conclusion: Baby massage assistance and education can improve sleep quality and influence LBW babies' growth in Samarida City.